A Field-based Approach to Teach Geoscience: A Study with Secondary Students. (2nd June 2015) - Esteves, Helena; Fernandes, Isabel; Vasconcelos, Clara
Abstract: Many geoscience fieldworks are not aligned with the curriculum contents reflecting the need to develop more research related to the outdoor learning environment. The purpose of the study was to verify if a fieldwork organized in accordance with Orion's model (1993), could be assumed as an integral part of formal school science curricula. A fieldwork has been carried with a sample of 115 secondary science students from a rural school in Portugal. A mixed research method was carried out. Short questionnaires were applied to students and to a participant observer, and the researcher wrote reports. Evidences indicated the relevance of geological fieldworks for geoscience education. This study highlighted the relevance of fieldwork as an integral component of the formal curriculum.